2015
DOI: 10.1371/journal.pone.0131902
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cross-Sectional Area and Transverse Diameter of the Heart on Inspiratory and Expiratory Chest CT: Correlation with Changes in Lung Size and Influence on Cardiothoracic Ratio Measurement

Abstract: ObjectiveThe aim of this study was to investigate physiological changes in cardiac area and diameters between inspiratory and expiratory chest computed tomography (CT), and to assess their correlation with lung size change and influence on cardiothoracic ratio (CTR) measurements.Materials and MethodsThe institutional review board of our institution approved this study, and informed consent was waived. Forty-three subjects underwent inspiratory and expiratory chest CT as part of routine clinical care. On both i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…In the current study, we used dynamic-ventilation CT to demonstrate that smokers without obvious airflow limitation have an incremental change in heart size during expiration, consistent with previous reports of non-COPD patients. 20 In subjects without airflow limitation, a rapid reduction in intrathoracic pressure during inspiration leads to an increase in venous return and an increase in right-sided cardiac volume. Meanwhile, reduced pulmonary venous return due to blood pooling in the lung parenchyma causes a reduction in left-sided cardiac volume.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the current study, we used dynamic-ventilation CT to demonstrate that smokers without obvious airflow limitation have an incremental change in heart size during expiration, consistent with previous reports of non-COPD patients. 20 In subjects without airflow limitation, a rapid reduction in intrathoracic pressure during inspiration leads to an increase in venous return and an increase in right-sided cardiac volume. Meanwhile, reduced pulmonary venous return due to blood pooling in the lung parenchyma causes a reduction in left-sided cardiac volume.…”
Section: Discussionmentioning
confidence: 99%
“…At each frame of the dynamic-ventilation CT, the cardiac CSA was measured semi-automatically by research software that had the same function as the CT scanner console. Based on a previously published method, 20 the following process was repeated in each subject: first, a threshold was set using Hounsfield units (HU) to exclude the pericardial fat pad (from 0 to 300 HU); second, at each time frame, all images that contained the heart were identified and the maximum cardiac CSA was determined; third, the boundary of the heart was traced and the maximum cardiac CSA was recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the cardiac diameter, but not the CTR, was significantly correlated with the left ventricular size, the well-known predictor of cardiovascular morbidity and mortality. However, there are several studies that emphasize the utility of CTR in different entities [27][28][29][30][31]. Even CTR values that are within normal limits were found to have clinical implication.…”
Section: Editorialmentioning
confidence: 99%